Enhancing Santriwati’s Islamic Literacy Through the LIT-CON Model of Women’s Fiqh Learning in Pesantren - Arif, Muhamad; Zekkari, Mohamed; Addawiyah, Robiatul (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The urgency of women’s fiqh learning lies in its role in enhancing female students’ Islamic literacy through well-structured implementation involving planning, execution, and evaluation. This study aims to analyze the implementation process of women’s fiqh learning in Islamic boarding schools, focusing on methods, techniques, and challenges faced by teachers. Using a qualitative case study approach, data were collected through semi-structured interviews, observations, and documentation, with analysis based on Yin’s framework and triangulation for validity.Findings show that implementation follows three main stages: planning, execution, and evaluation. During the execution stage, teachers apply five steps: orientation/initial stimulation, problem identification, critical literacy, taking action, and evaluation. A teacher-centered approach is optimized alongside traditional pesantren methods such as sorogan, bandongan, and musyawaroh, integrated with interactive lectures, discussions, and question-and-answer techniques. This combination provides both theoretical understanding and practical engagement for female students. The research highlights the theoretical implication of a Literacy-Based Constructivism Learning Model (LIT-CON Model), which strengthens literacy depth and creates space for critical thinking among female students. The practical implication recommends pesantren develop constructivism-based curricula to ensure fiqh learning goes beyond turath (theoretical knowledge) and is understood deeply and contextually, aligning with contemporary challenges. Teachers face challenges in contextualizing women’s fiqh while maintaining traditional approaches, yet innovative integration of methods supports meaningful literacy improvement. Thus, women’s fiqh learning is not only essential for preserving Islamic tradition but also for equipping female students with critical, contextualized understanding relevant to modern times.